ANALISIS USAHA PADA USAHA TAMBAK UDANG WINDU BERKAT YAKIN DI DESA PENAMPI KABUPATEN BENGKALIS - Sari, Kartika Sari Kartika; ', Makhdalena; ', Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : The purpose ofthis research was toanalyzethe cost ofproduction, revenue, profitandefficiencylevel of Berkat Yakin shrimp pond in Penampi village of Bengkalis distric. This research was in Berkat Yakin shrimp pondin Penampi village of Bengkalis distric.The data usedin this researchis a type ofsecondary datawithinterviewdata collection techniquesanddocumentationfrom2011-2013. Data analysis technique used in this research is qualitative descriptive. The results showed that in 2011 enterprise Berkat Yakin shrimp pond has a value that is equal to Rp 1.49 efficiency. Then, In 2012 enterprise Berkat Yakin shrimp pond has a value that is equal to Rp 1.85 efficiency and at the 2013enterprise Berkat Yakin shrimp pond has a value that is equal to Rp 2.16 efficiency. It can be summarized that this business has efficiency level more than one, which is means that this business is worthto be developedorcan be forwarded.Keywords: Business, shrimp pond